Comparison of five portable peak flow meters - Takara, Glaucia Nency (2010)
OBJECTIVE: To compare the measurements of spirometric peak expiratory flow (PEF) from five different PEF meters and to determine if their values are in agreement. Inaccurate equipment may result in incorrect diagnoses of asthma and inappropriate treatments. METHODS: Sixty-eight healthy, sedentary and insufficiently active subjects, aged from 19 to 40 years, performed PEF measurements using Air Zone®, Assess®, Galemed®, Personal Best® and Vitalograph® peak flow meters. The highest value recorded for each subject for each device was compared to the corresponding spirometric values using Friedman's test with Dunn's post-hoc (p